2012
DOI: 10.1620/tjem.226.221
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Second Intron of the FGFR2 Gene Are Associated with the Risk of Early-Onset Breast Cancer in Chinese Han Women

Abstract: Fibroblast growth factor receptor 2 (FGFR2) plays an important role in tumor cell growth, invasiveness, motility, and angiogenesis. Several single-nucleotide polymorphisms (SNPs) in the second intron of the FGFR2 gene are associated with the risk of breast cancer. In this study, we determined whether these SNPs of the FGFR2 gene are associated with early onset of non-familial breast cancer in a Chinese Han population. Recruited were 118 female breast cancer patients who were less than or equal to 35 years of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
6
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
6
6
0
1
Order By: Relevance
“…However, limited researches have been done on the impact of rs1219648 on early onset breast cancer. Although the recent study by Chun-Lian Liu and coworkers has been refused the impact of rs1219648 in premenopausal breast cancer (Liu et al, 2013), in another investigation carried out on Chines Han woman a great association appeared between rs1219648 and premenopausal breast cancer (Fu et al, 2012). In our study the association between the G allele of rs1219648 FGFR2 and early onset breast cancer is in agreement with the aforementioned study (p=0.006).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, limited researches have been done on the impact of rs1219648 on early onset breast cancer. Although the recent study by Chun-Lian Liu and coworkers has been refused the impact of rs1219648 in premenopausal breast cancer (Liu et al, 2013), in another investigation carried out on Chines Han woman a great association appeared between rs1219648 and premenopausal breast cancer (Fu et al, 2012). In our study the association between the G allele of rs1219648 FGFR2 and early onset breast cancer is in agreement with the aforementioned study (p=0.006).…”
Section: Discussionsupporting
confidence: 91%
“…Five single nucleotide polymorphisms (SNP) of FGFR2 gene are associated with breast cancer (Katoh, 2008 other SNPs, the role of rs1219648 (IVS2±7033A>G) in postmenopausal breast cancer is more remarkable (Hunter et al, 2007;Zhang et al, 2010a). Despite this clear evidence some researches stress on the effect of this polymorphism on premenopausal breast cancer (Fu et al, 2012). Genetic alterations of FGFR2 cause aberrant activation of FGFR2 signaling in breast cancer (Katoh, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In this case-control study of BC in Pakistani women, significant associations were observed between two SNPs of FGFR2 [rs1219648: P=9.08e-006 (GG, P=0.000087, AG, P=0.000018) and rs2981582: P= 0.005 (CT, P= 0.001, TT, P= 0.097)]. These results are consistent with results obtained from other Asian regions, including China (16,32,37), Japan (38) and India (18). Furthermore, the SNPs rs1219648 and rs2981582 of FGFR2 have been consistently associated with BC risk in several other ethnic groups, including European (39), Hispanic and non-Hispanic Caucasian women from Southwestern United States (40), African American (29,41) and Tunisian (42) women populations.…”
Section: Discussionsupporting
confidence: 89%
“…However, similar SNPs do not show any association with the risk of BC in women of African ancestry (29)(30)(31). Taken together, the novel genetic variants of the genes FGFR2, MAP3K1 and TNRC9 have shown a marked association with BC in populations of diverse ethnicity (32), and the variants identified as BC risk factors have revealed a variable impact on the risk of BC associated with different populations. Hence, the replications of previously BC associated loci in multiple populations are required to explore the genetic heterogeneity of BC (18).…”
Section: Introductionmentioning
confidence: 90%
“…Ahsan et al [1], for example, reported genome-wide significant p-values for 4 FGFR2 SNPs and young-onset breast cancer, with the smallest p-value seen for rs2981579. Other studies have also observed associations between FGFR2 SNPs and young-onset breast cancer [41, 42, 69, 74]. …”
Section: Methodsmentioning
confidence: 92%